2013
DOI: 10.1021/es3050696
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Fate of Microbially Sequestered Carbon Dioxide in Soil Organic Matter

Abstract: The microbial contribution to soil organic matter (SOM) has recently been shown to be much larger than previously thought and thus its role in carbon sequestration may also be underestimated. In this study we employ (13)C ((13)CO₂) to assess the potential CO₂ sequestration capacity of soil chemoautotrophic bacteria and combine nuclear magnetic resonance (NMR) with stable isotope probing (SIP), techniques that independently make use of the isotopic enrichment of soil microbial biomass. In this way molecular inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 78 publications
2
23
0
Order By: Relevance
“…A contribution of phototrophic and chemoautotrophic microorganisms to SOM has been demonstrated already by other studies (Hart et al, 2013;Yuan et al, 2012), but solely for top soils. Wu et al (2014Wu et al ( , 2015 investigated soil depth profiles up to 15 cm depth , but found no significant incorporation below 5 cm depth in upland and paddy soils under not manipulating experimental conditions, like illumination.…”
Section: Importance Of Co 2 Fixation For Soil Carbon In Reference Soilssupporting
confidence: 56%
See 1 more Smart Citation
“…A contribution of phototrophic and chemoautotrophic microorganisms to SOM has been demonstrated already by other studies (Hart et al, 2013;Yuan et al, 2012), but solely for top soils. Wu et al (2014Wu et al ( , 2015 investigated soil depth profiles up to 15 cm depth , but found no significant incorporation below 5 cm depth in upland and paddy soils under not manipulating experimental conditions, like illumination.…”
Section: Importance Of Co 2 Fixation For Soil Carbon In Reference Soilssupporting
confidence: 56%
“…Direct uptake of CO 2 into microbial biomass (MB) and soil organic matter (SOM) by photoautotrophic and chemoautotrophic organisms has been measured in paddy rice and agricultural upland soils (Liu and Conrad, 2011;Wu et al, 2015Wu et al, , 2014 as well as under manipulating experimental conditions, such as H 2 amendment (Stein et al, 2005) or addition of reduced sulfur compounds (Hart et al, 2013). Autotrophic acetogenic organisms, using the Wood-Ljungdahl pathway for CO 2 fixation, are important groups in wetland and forest soils (Küsel and Drake, 1995;Ye et al, 2014).…”
Section: E Nowak Et Al: Autotrophic Fixation Of Geogenic Co 2 Bymentioning
confidence: 99%
“…eutropha, which is well-known for its contribution to carbon sequestration in soil through the production of polyhydroxyalkanoates. 35 On the basis of the kinetic properties of the RubisCO forms, it is generally believed that form II RubisCO favors high-CO 2 (1.5%) and low-O 2 conditions while form I RubisCO is more active under aerobic conditions and in low-CO 2 environments. 33 The multiple RubisCO gene sets can help microorganisms to survive in a dynamic environment such as paddy soils, with respect to the switching between aerobic and anaerobic conditions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Previously, we showed that the addition of thiosulfate to soils resulted in an order of magnitude increase in the uptake of CO 2 by chemoautotrophs 12, 13 . Thiosulfate acts as an electron donor and provides the energy for a large increase in CO 2 uptake.…”
Section: Introductionmentioning
confidence: 95%